Gain of 1q21 and distinct adverse cytogenetic abnormalities correlate with increased microcirculation in multiple myeloma - Hillengaß, Jens; Zechmann, Christian; Nadler, Andreas Marc; Hose, Dirk; Cremer, Friedrich Walter; Jauch, Anna; Heiß, Christiane; Benner, Axel; Ho, Anthony Dick; Bartram, Claus R.; Kauczor, Hans-Ulrich; Delorme, Stefan; et al. (International journal of cancer, 2008)
To identify genetic mechanisms controlling bone marrow microcirculation and angiogenesis in patients with plasma cell disease we simultaneously performed bone marrow dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) and cytogenetics (iFISH) on CD138 purified plasma cells of MGUS (n=31) and untreated multiple myeloma (MM) (n = 87) patients. The adverse cytogenetic abnormalities gain of 1q21, deletion 17p13 and deletion 13q14 significantly correlated with at least one DCE-MRI finding (aberrant “focal” microcirculation pattern, increase in median microcirculation parameter Amplitude A or exchange rate constant kep). We conclude that gain of 1q21, deletion 13q14 and deletion 17p13 trigger the angiogenic cascade in MM. Our findings will have important implications for the design, analysis and stratification for clinical studies of patients with MM in particular if compounds with antiangiogenic activity are used. © 2008 Wiley-Liss, Inc.